Split hand-split foot-ectodermal dysplasia and amelogenesis imperfecta with a TP63 mutation - Kantaputra P.N. (2014)
We report on a mother and son who were affected with split hand-split foot (formerly described as ectrodactyly), ectodermal dysplasia, hyperpigmentation of skin, and dystrophic nails. Their hair was wiry, brownish, and slow-growing. Scanning electron micrography of their scalp hair showed hypoplastic hair bulbs, partial loss of hair cuticles, and frayed hair shafts. The son was affected with amelogenesis Imperfecta (hypocalcification, hypoplasia, and hypomaturation types), in the primary and permanent dentition. An unerupted supernumerary maxillary second premolar and fusion of mandibular incisors were observed in the primary dentition and their permanent successors. Mutation analysis showed a c.588-2A>C mutation in TP63 in the mother and her son. It is predicted that an alternative splice site was used, specifically the AG located just three nucleotides upstream. Use of this site is predicted to include three extra nucleotides in the transcript and thus incorporation of a single extra amino acid (p.Thr195-Tyr196insPro). This is the first time that amelogenesis imperfecta, fusion of teeth, and a supernumerary premolar have been shown to be associated with a TP63 mutation. © 2011 Wiley Periodicals, Inc.